Factors associated with induced abortions in Pakistan: a comprehensive analysis of Pakistan maternal mortality survey 2019 - Khalid, Samina Naeem; Midhet, Farid; Uzma, Qudsia; Thom, Ellen Mpangananji; Baqai, Shehla; Khan, Muhammad Talha; Memon, Areeba (Frontiers in Reproductive Health, 2025)
BackgroundInduced abortions (IA) remain a serious public health issue in Pakistan despite social constraints and legal prohibitions. The number is alarmingly high, and the study done by the Population Council (2012) indirectly estimated 2.2 million abortions per year and an abortion rate of 50 per 1,000 women.MethodologyThis study reports the results of a secondary data analysis of the Pakistan Maternal Mortality Survey 2019 to compare the women who reported having an IA in the last three years with those having a live birth in the same period. A nested case-control comparison of women reporting IA as cases and those having a live birth as controls. Logistic regression was used to estimate odds ratios (OR) for major risk factors of maternal mortality after adjusting for women's age, parity, education, and wealth quintile.ResultsResults show that recent use of family planning, having a prior history of pregnancy loss, and higher gravidity are all linked to IA (P < 0.05). On the other hand, neither the average household education nor the women's education affects the rates. The other associated factors include parity, past use of family planning, socioeconomic status, place of residence, and the educational level of women. These correlations are based only on uncorrected odds ratios and do not account for confounding variables.ConclusionWomen having past miscarriages, having several children, or improperly using family planning methods are more likely to have induced abortions. These findings can help medical professionals develop evidence-based policies and regulations.